The Value of Children for Low Income Families in Yogyakarta - Umi Listyaningsih; Nanda Muliansah; Dwi Lestari; Sri Rum Giyarsih (Jurnal Ilmu Sosial dan Humaniora, 2024)
Economics is a factor that influences the decision to have children. The cost of caring for, raising, and educating children is one aspect of managing births. However, in rural farming communities, families have the advantage of having many children. They can function as family workers in the agricultural sector. Gunungkidul Regency, a rural area of ​​Yogyakarta with a majority agricultural sector, has a total fertility rate of 1.96 (2020 Population Census). Around 15.6 percent of Gunungkidul residents are below the poverty line. Why does Gunungkidul Regency have a low fertility phenomenon while the environment and population characteristics allow for high fertility? The results of a qualitative study of low-income families show that they do not want to inherit poverty. Limited access to education, loss of happy childhood times because they have to work, and the destruction of hopes and desires. This condition is very burdensome and hurts feelings. Education is one way to avoid being poor. The hope is to get a formal job with a steady income. Limiting births is a way for children to get maximum education. The geomorphological conditions of the mountains cause limited accessibility when there is no means of transportation. Parents do not expect their children to return the favor in the future. Caring for and raising children responsibly is a parent's obligation. Determining the number of children to have depends on the wishes and abilities of the parents.